Vital signs should be maintained as continuous variables when predicting bacterial infections in febrile children. - Spruijt, B; Vergouwe, Y; Nijman, R; Thompson, M; Oostenbrink, R (2013)
OBJECTIVE: To determine how vital signs such as heart and respiratory rates should be included in prediction models for serious bacterial infections (SBIs) in febrile children. STUDY DESIGN AND SETTING: Prospective observational study of 1,750 febrile children aged <16 years, visiting the emergency department of a university hospital; of them 13% (n = 222) had SBI. Common age-specific thresholds of heart and respiratory rates were used to define tachycardia and tachypnea. We compared seven strategies to handle vital signs as predictors of SBI (dichotomized or continuously in various ways). RESULTS: The dichotomous predictors, namely tachycardia and tachypnea, containing information on the vital sign and age showed limited value to predict the presence of SBI (area under the receiver operating characteristic curve [AUC (ROC)]: 0.53 for heart rate and 0.55 for respiratory rate). In comparison, a model with age as a single continuous predictor resulted in an AUC of 0.58. Models with age and one of the vital signs included continuously showed the highest AUC (heart rate: 0.60 and respiratory rate: 0.63). CONCLUSION: Heart and respiratory rates should be maintained as continuous variables in model development to predict SBI in febrile children, as dichotomization results in information loss and lower predictive ability.